Global Roadmap for Circular Economies: The Integration of Digital Innovation, Governance, and Sustainable Development Goals (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The global shift toward a circular economy offers significant opportunities for sustainable development but also poses key challenges. This article presents a roadmap that integrates digital innovation, governance frameworks, and alignment with the Sustainable Development Goals to accelerate circular economy adoption worldwide. Critical technologies such as the Internet of Things, artificial intelligence, blockchain, and big data analytics are identified as enablers for resource tracking, process optimization, and material traceability. The roadmap highlights the importance of policy development, digital infrastructure investment, stakeholder education, and international collaboration, supported by robust monitoring mechanisms. Case studies across manufacturing, logistics, energy, and smart cities illustrate practical applications and scalability. Finally, the article addresses barriers including regulatory gaps, the digital divide, and cultural challenges and offers policy recommendations to foster sustainable, resilient, and inclusive circular economies.